Design and analysis aspects of radial flux air-cored permanent magnet wind generator system for direct battery charging applications - Stegmann, Johannes Abraham (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.